Athlete mental health: Responding on the front lines - Cogan, K. (Olympic & Paralympic Coach, 2020)
We are all responsible for athlete mental health. "What?" you say, "I am not a mental health profes-sional. How do I help with athlete mental health?" That may be true, but we all have a role to play, and we are in this together. When athletes are struggling with anything, including mental health concerns, they will most likely go to someone they trust, and often that is you, their coach. Coaches are on the front lines and need to be prepared to listen and help. You don`t have to know how to treat a men-tal health concern. You do need to know how to talk about it and refer to the right resources. Mental health concerns can arise for anyone in the sport world, so it may not be only the athletes who need support. It could be coaches, support staff, parents or medical staff. No one is immune to the pres-sures of life and sport, and we need to be aware of signs and symptoms that can affect anyone.This article will outline the process of recognizing, talking about and finding resources when someone you know is facing a mental health concern. We`ll (a) examine some facts and statistics about mental health, (b) discuss mental health and mental illness, (c) review symptoms of common mental illness-es, (d) learn how to ask about symptoms, including thought of self-harm and suicide, and (e) know how to find the necessary resources for anyone in need. You may be on the front line, but you don`t have to face this alone.